Geometric magnetism and the heavy ion spin-orbit interaction - Sukumar, C; Brink, D (1998)
Geometric magnetism is a term used for describing the leading corrections to the adiabatic approximation to a quantal system. In this paper we apply these ideas to a heavy ion collision and show that the leading correction to the static polarization potential is an induced spin-orbit interaction. We derive an explicit expression for its strength. © 1998 Elsevier Science B.V.